Long-term safety and efficacy of apomorphine infusion in Parkinson's disease patients with persistent motor fluctuations: Results of the open-label phase of the TOLEDO study. (February 2021) - Katzenschlager, Regina; Poewe, Werner; Rascol, Olivier; Trenkwalder, Claudia; Deuschl, Günther; Chaudhuri, K Ray; Henriksen, Tove; van Laar, Teus; Lockhart, Donna; Staines, Harry; Lees, Andrew
Abstract: Introduction: The randomized, double-blind phase (DBP) of the TOLEDO study confirmed the efficacy of apomorphine infusion (APO) in reducing OFF time in PD patients with persistent motor fluctuations despite optimized oral/transdermal therapy. Here we report safety and efficacy results including the 52-week open-label phase (OLP). Methods: All patients completing the 12-week DBP (including those switching early to open-label treatment) were offered OLP entry. The primary objective was the evaluation of long-term safety of APO. Results: Eighty-four patients entered the OLP (40 previously on APO, 44 on placebo) and 59 patients (70.2%) completed the study. The safety profile of APO was consistent with experience from extensive clinical use. Common treatment-related adverse events (AEs) were mild or moderate infusion site nodules, somnolence and nausea. Fourteen (16.7%) patients discontinued the OLP due to AEs, those involving >1 patient were infusion site reactions (n = 4) and fatigue (n = 2); hemolytic anemia occurred in one case. Reduction in daily OFF time and improvement in ON time without troublesome dyskinesia were sustained for up to 64 weeks. Pooled data for week 64 (n = 55) showed a mean (SD) change from DBP baseline in daily OFF time of −3.66 (2.72) hours and in ON time without troublesome dyskinesia of 3.31 (3.12) hours. Mean (±SD) daily levodopa-equivalent dose decreased from DBP baseline to week 64 by 543 mg (±674) and levodopa dose by 273 mg (±515). Conclusions: The safety and efficacy of APO infusion were demonstrated with long-term use for persistent motor fluctuations, allowing substantial reductions in oral PD medication. Highlights: TOLEDO demonstrated the efficacy of apomorphine infusion for motor fluctuations in PD. The open-label phase over up to 64 weeks showed no unexpected safety signals. Reduced OFF and increased ON time without troublesome dyskinesia were sustained. Patient global impression of change remained improved. Apomorphine infusion led to substantial reductions in oral PD medication.